2022
DOI: 10.1101/2022.08.19.504549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-dependent enhancement in ventral tegmental area dopamine neuron activity drives pain-facilitated fentanyl intake in males

Abstract: Pain affects over 50% of US adults. Opioids are potent analgesics used to treat pain symptoms but are highly prone to abuse, creating a major dilemma for public health. Evidence suggests that the proclivity for opioid abuse under pain conditions varies between sexes. However, the neural mechanisms underlying sex-specific effects of pain on opioid use are largely unclear. Here, we recapitulate clinical findings and demonstrate that pain increases self-administration of the widely abused opioid, fentanyl, select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Regarding mesoaccumbal circuitry, a sex-and time-dependent adaptation to VTA DA cell activity has been reported by Jones and colleagues, with opioid-evoked phasic activity of DA cells bidirectionally changing across a three-week period of opioid exposure in males 59 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Regarding mesoaccumbal circuitry, a sex-and time-dependent adaptation to VTA DA cell activity has been reported by Jones and colleagues, with opioid-evoked phasic activity of DA cells bidirectionally changing across a three-week period of opioid exposure in males 59 .…”
Section: Discussionmentioning
confidence: 76%
“…Regarding mesoaccumbal circuitry, a sex- and time-dependent adaptation to VTA DA cell activity has been reported by Jones and colleagues, with opioid-evoked phasic activity of DA cells bidirectionally changing across a three-week period of opioid exposure in males 59 . Additionally, Jones and colleagues have shown that long-access heroin self-administration enhances phasic DA release in the medial NAc shell but not core subregion in females, with males displaying no difference in either subregion 53 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These sex differences seem to be in accordance with a recent report showing that pain does not alter the dose response for fentanyl self-administration in female rats. 12 Previous studies have shown differential effects of pain on drug seeking in a sex-dependent manner. 12 , 30 Therefore, it is likely that similar pain-induced sex-dependent effects may be observed in alcohol drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an interaction of chronic pain and sex on opioid motivation, in which SNI females showed greater motivation for opioids with increasing effort. Other work with a complete Freund's adjuvant injury led to increased intravenous fentanyl self-administration in male, but not female rats [47], while exposure to morphine shows no difference during the acquisition phase between SNI and sham animals [44]. However, authors looking at various intravenous opioids, including fentanyl, found that male rats with a spinal nerve ligation self-administered less than sham animals at lower doses, but similar amount of infusions at higher doses [12].…”
Section: Discussionmentioning
confidence: 99%